Quality of Life and Social Inclusion in Child Development Centers of the Ministry of Social Development of Buenos Aires - Masi, Paula; Campoya, Natalia; Gómez, Melany; Bernardo Samuel, Kerman (European Scientific Journal, ESJ, 2017)
The general purpose of this study was to perform an exploratory and descriptive analysis of Quality of life and social inclusion in Child Development Centers (CEDI) of the Ministry of Social Development of tBuenos Aires.. The sample is of 600 people in attendance at the Child Development Centers. The specific aim is to determine the families’ perception about their quality of life and about their social inclusion based on scales and indicators and the evaluation of modifications after the process in the CEDIS. The variable to be measured in this study is the quality of life in this population. The instrument, Quality of Life Questionnaire, WBIInternational Well Being Group. Translation Tonón & Aguirre (2009). Sociodemographic data are also evaluated. From the application of the scale the following conclusions are reached: There are no significative differences between the levels of quality of life , the sex and the age of the participants. We analyzed whether there are relations between the levels of quality of life with respect to the number of people living together, which were not found; regarding current economic levels, there are statistically significant differences (at a higher current economic level, higher levels of quality of life); compared with economic level three years ago, there are statistically significant differences (those who are better economically at present compared to three years ago, have higher levels of quality of life), religiosity, no differences; educational level , there are no differences; satisfaction with CEDI, there are statistically significant differences (the higher satisfaction with the inclusion of the child in CEDI, higher levels of quality of life).